2018
DOI: 10.1111/ans.14870
|View full text |Cite
|
Sign up to set email alerts
|

When does curatively treated colorectal cancer recur? An Australian perspective

Abstract: Background: While most colorectal cancer (CRC) recurrences reportedly occur within 3 years following curative treatment, many studies are limited by short-term follow-up. This study examines the time to recurrence of CRC in a large Australian cohort with a long follow-up period and assesses whether time to recurrence has changed over time.Methods: A comprehensive prospective database of patients undergoing resection for CRC is maintained at Concord Hospital, Sydney. Demographic and time to recurrence data were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
6
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 33 publications
0
6
0
Order By: Relevance
“…Between 70% and 90% of the recurrences are detected within the first 3 years after surgery. [2][3][4][5][6][7][8][9] In Denmark and many other countries, CRC recurrence is not recorded routinely in clinical databases or nationwide healthcare registries. Therefore, Lash et al developed and validated an algorithm combining data from different Danish registries to identify CRC recurrences for the period 2001-2011.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Between 70% and 90% of the recurrences are detected within the first 3 years after surgery. [2][3][4][5][6][7][8][9] In Denmark and many other countries, CRC recurrence is not recorded routinely in clinical databases or nationwide healthcare registries. Therefore, Lash et al developed and validated an algorithm combining data from different Danish registries to identify CRC recurrences for the period 2001-2011.…”
Section: Introductionmentioning
confidence: 99%
“…Three years of complete follow-up would be preferable as 90% of all recurrences occur within this timeframe. [2][3][4][5][6][7][8][9]…”
mentioning
confidence: 99%
“…Specifically, our cohort was divided into those ≤2 years from their index surgery and those who were >2 years. A cutoff of 2 years was chosen as studies have demonstrated that over 50% of CRC patients recur within this time frame [23]. Optum software was used to transform SF‐36v2 question answers into norm‐based PCS and MCS scores.…”
Section: Methodsmentioning
confidence: 99%
“…Approximately 20%–25% of patients present with synchronous metastases, and a significant proportion of stages I–III will develop metachronous metastases (MM) 2–7 . These are mainly detected during the first 3 years after primary surgery 8 …”
Section: Introductionmentioning
confidence: 99%